Angiogenesis in malignant ovarian tumors after menopause: usefulness of pericytes immunohistochemic evaluation and microvessels density - Czekierdowska, Sylwia; Czekierdowski, Artur (Menopause Review/Przegląd Menopauzalny, 2006)
Material and methods: We compared microvessel density (MVD) and pericytes expression in malignant ovarian tumors of 45 postmenopausal and 32 premenopausal women who were operated in the Ist Department of Gynecology of Medical University in Lublin between 2002 and 2004. Immunohistochemistry was performed and MVD was assesed with the use of anti CD34 antibody (Dako, Denmark), whereas pericytes were detected with anti-smooth muscle actin (alphα-SMA) and anti-desmin specific monoclonal antibodies. Results: Additionally, the so called pericytes coverage index (PCI) was calculated for each tumor. MVD was significantly higher in malignant tumors of postmenopausal women when compared to premenopausal patients (p<0.005). Medians of pericytes as measured with alphα-SMA or desmin were not significantly different between the groups. Desmin expression was highly correlated with alphα-SMA expression (R=0.61, p<0.0001). The median number of desmin-positive cells per high-power field was 4,8 (range: 0.0-25.8), however, in 12 tumors (including 3 postmenopausal women) there was no positive staining with anti-desmin antibody. Malignant tumor median pericyte density assessed with alphα-SMA was 10,5 (range: 2.7-47.0). There was a positive correlation of MVD-CD34 and pericytes median numbers for both alphα-SMA (R=0,57; p<0.0001) and desmin (R=0.40; p=0.0002). A negative correlation between MVD and PCI as measured with alphα-SMA was also found (R=-0.35; p=0.001). Conclusions: We conclude that regardless of the women’s menopausal status the assessment of pericytes expression and microvessel density may be used in the malignant ovarian tumors angiogenic characterization.